Smoldering Ashes : Cuzco and the Creation of Republican Peru, 1780-1840 - Walker, Charles F., 1959- (Book collections on Project MUSE., 1999)
Reconsiders Peru's transition from colony to republic, highlighting the important role indigenous peasants played in anti-colonial struggles.